Interface of teaching foreign languages and university outreach in the context of the Covid-19 pandemic - Aguiar Bellido, Jorge David; da Silva Filomena, Bárbara; dos Santos Gomes, Henrique; Pena Natividade , Flaviana (Guará Journal, 2023)
This article presents an experience report on the “CAP Langua-ge  Conversation  Center,”  an  outreach  project  initiated  by  the  Federal University of São João del Rei, Alto Paraopeba campus, aimed  at  democratizing  the  knowledge  of  foreign  languages  through  cultural  and  teaching  activities.  The project  has  been  active  since  2014  and  focuses  on  sensitizing  society  to  the  importance of learning a second language and promoting internationalization.  Amidst  the  COVID-19  pandemic,  the  project  observed  a  significant  increase  in  the  number  of  courses  and  classes  offered,  as well  as  the  team  size  and  enrollment  of  in-dividuals in the selection process. Compared to the 2020.1 and 2022.1 public calls, the number of students enrolled increased by  533.75%.  The  article  aims  to  investigate  the  impact  of  the  language  courses  offered  by  the  project.  Analyzing  the  data collected from each public call, it was evident that the project garnered  greater  visibility  for  both  the  project  and  UFSJ,  ena-bling participation from individuals from other universities and states in Brazil, fulfilling its objective of outreach in knowledge diffusion.
Keywords: University outreach; COVID-19; Communication; Language teaching; Social distancing